2015
DOI: 10.1007/s13213-015-1155-5
|View full text |Cite
|
Sign up to set email alerts
|

The internal bacterial diversity of stored product pests

Abstract: Symbiotic bacteria associated with insects play important roles in different physiological processes such as digestion, insect behavior, defense and providing essential nutrition in insect gut. In addition, these bacteria can be used in biocontrol of insect pests using genetic engineering techniques. The first step is to isolate and identify symbiotic bacteria from insects to elucidate their roles, and to use in the development of transgenic strains. For this purpose, we isolated and characterized the bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…The Pantoea is a member of the Enterobacteriaceae, with more than 20 species, which are adapted to diverse ecological niches, including humans, insects, plant material, soil, and water (Walterson and Stavrinides, 2015). It has been reported to colonize in several Lepidopteran species (Broderick et al, 2004;Robinson et al, 2010;Pinto-Tomás et al, 2011;Tang et al, 2012;He et al, 2013;Chen et al, 2016;Sevim et al, 2016). Recent studies have shown that Pantoea species contribute tothe provision of essential nutrients limited in the host's diet (Kenyon et al, 2015), participating in creating a nitrogen-rich environment for developing eggs and larvae (MacCollom et al, 2009) and the breakdown of plant cell-wall biopolymer (Bozorov et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The Pantoea is a member of the Enterobacteriaceae, with more than 20 species, which are adapted to diverse ecological niches, including humans, insects, plant material, soil, and water (Walterson and Stavrinides, 2015). It has been reported to colonize in several Lepidopteran species (Broderick et al, 2004;Robinson et al, 2010;Pinto-Tomás et al, 2011;Tang et al, 2012;He et al, 2013;Chen et al, 2016;Sevim et al, 2016). Recent studies have shown that Pantoea species contribute tothe provision of essential nutrients limited in the host's diet (Kenyon et al, 2015), participating in creating a nitrogen-rich environment for developing eggs and larvae (MacCollom et al, 2009) and the breakdown of plant cell-wall biopolymer (Bozorov et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…and Staphylococcus sp. (Sevim et al, 2016). Similarly, PrabhaKumari et al (2011) studied the microflora of the red flour beetle (Tribolium castaneum) and isolated different bacteria including Staphylococcus, Pseudomonas, Bacillus, Escherichia and Enterobacter sp.…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%
“…For this reason, the study of the bacterial community that is associated with stored product pests is important, but to date, the scope has been very limited and based mostly on culture-dependent approaches. The few studies that have investigated stored product pests focused on insects (e.g., in Tribolium castaneum , Liposcelis bostrychophila , Acanthoscelides obtectus , Callosobruchus maculatus , Sitotroga cerealella , and Phthorimaea operculella [ 111 , 112 , 113 , 114 ]) and mites (e.g., Tyrophagus putrescentiae [ 115 , 116 ]).…”
Section: Microbiota Of Moth Pestsmentioning
confidence: 99%
“…These OTUs were assigned to the genera Propionibacterium , Corynebacterium , Streptococcus , Acinetobacter, and Staphylococcus . Interestingly, Sevim and colleagues [ 114 ], using a culture-dependent approach, isolated 17 Staphylococcus strains from four stored product pests ( Acanthoscelides obtectus , Callosobruchus maculatus , Sitotroga cerealella, and Phthorimaea operculella ) reared on different substrates (beans, kidney beans, corn, and potatoes, respectively). Despite the small number of studies related to the bacterial communities associated with these insects, the results from the reported studies show that the genus Staphylococcus seems to be commonly associated with stored product pests and could represent a possible target for developing some biocontrol strategies, since it is possible to genetically modify bacteria of this genus [ 127 ].…”
Section: Factors Affecting the Moth Microbiotamentioning
confidence: 99%